Karakteristik Sensoris dan Kimia Penyedap Rasa Berbahan Dasar Tepung Tempe Gembus dengan Penambahan Gula dan Garam - Afifah, Raudhatul; Listyaningrum, Ratna Sari; Amelianawati, Mae (LPPM Universitas Terbuka, 2024)
Gembus tempeh flour contains high levels of glutamate which can be used as a flavoring. The aim of this research is to determine the sensory and chemical characteristics of the flavoring ingredients of tempe gembus flour. The formulation ingredient for this research product is tempeh gembus from tofu dregs from the Cibuntu tofu making industry. Flour is made by curing tempeh for 3 days at 35°C, then slicing and drying at 70°C for 2 hours, then grinding and sifting using 80 mesh. The formulation was determined through two stages of sensory testing. Phase I sensory testing included the Duo-Trio differentiation test and hedonic test, using two samples of tempeh gembus flour formulation and a commercial MSG product as a control. Preferences are assessed using the parameters of color, aroma, taste and overall rating. Analysis of data from the differentiation test results uses the Chi-square test, while analysis of hedonic test data uses the Mann-Whitney test. The results of the phase I sensory test were used as a control in the phase II sensory test and compared with the sugar-salt addition formulation with a ratio of tempe gembus flour, salt and sugar of 5:3:2. Chemical testing was carried out which included testing water content, salt content and protein content. The test results showed that the sample with added sugar and salt had a water content of 4.6%, a salt content of 22.56%, a protein content of 7.74%, and panelists preferred sensory properties compared to the control.